Introduction to 1983 Paris Congresses - Wheeler, Barbara (Voices: A World Forum for Music Therapy, 2009)
The Paris World Congresses of Music Therapy were important to the development of the World Federation of Music Therapy. They also both convey some of the confusion that it seems existed because of the two associations in France at the time and the fact that there were two conferences that year. The interviews and other contributions in this issue of Voices will shed light on these important events.